PERAN IBU DALAM PENDIDIKAN KARAKTER ANAK MENURUT PANDANGAN ISLAM - Sri Mulyani (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2018)
This article elaborates the important roles of mothers in children’s character education according to Islamic perspectives. Character education is absolutely important by all the glory of man lies in his character. The formulation of important issues to be discussed is the importance of family education, the maternal virtue in Islamic view and the mother’s role in shaping the character of children. Family education is very important in Islam, since family is the main pillar for the formation of children's character. In family education, mothers hold a central role as primary and first educators. The posititon of the mother in Islamic view is glorius. As a proof of noble posititon of the mother in Islamic teaching, a mother is entitled to devotion of a child as much as three times more than the father. Mothers play crucial roles in shaping the chacarter of children. To perform such a noble task, mothers can do things like: providing prenatal education, giving good examples to children, instilling good characters from childhood such as honesty, discipline and responsibility; and building good communication between mother and child.